Ear Findings in Post Surgical Cleft Palate Patients - Thakur, Sanjeev Kumar; Yadav, Baleshwar; Bedajit, Raj Kumar; Shrestha, Kailash Khaki; Rai, Shankar Man (Birat Journal of Health Sciences, 2019)
Introduction: Cleft lip and palate is one of the most common congenital anomaly, which contributes to eustachian tube dysfunction leading to impaired middle ear ventilation and middle ear pathology. It has been stated that the timely repair of cleft palate reduces the incidence of otitis media with effusion.Objective: To describe the ear findings in cleft palate patients who have undergone repair of cleft palate.Methodology: A total of 36 (20 male and 16 female) post cleft repair patients underwent Otoscopy and Tympanometry between January to December 2018. Cases with isolated cleft lip, ears with perforation of tympanic membrane and attico-antral disease were excluded.Results: The age range was from 4 years to 24 years, with a mean of 11.34 years. Maximum patients were of the age group of 10- 20 years (18, 50%) followed by that of 5-10 years range (15, 41.66%). Total number of ears examined were 72. Out of a total of 72 ears, 70 (97.2%) had abnormal otoscopic finding with dull tympanic membrane in 37 (51.39%) ears, retracted in 31 (43.05%) and bulging tympanic membrane in 2 (2.78%) cases. Type B curve was the commonest (36, 50%), followed by Type As (24, 33.3%). Type C curve was found in 11(15.3%) ears. Type A curve was found only in one ear. The duration of post-repair of cleft palate ranged from 6 months to up to 16 years with a mean of 8.52; 11 cases(30.56%) had history of repair of cleft palate of more than 10 years duration.16 cases (44.44%) had that of more than 5 years and 9 cases (25%) had less than 5 years history of duration of repair. When correlation was done statistically, the tympanometry findings and duration of repair had a very low correlation (Table 5). The time period of repair had no significant effect on tympanometric ear findings.Conclusion Abnormal otoscopic findings and tympanometric findings were common in post cleft palate repaired patients. The duration of cleft palate repair had low correlation to the tympanometric ear findings.